Meme as a History Learning Media in The Post-Millennial Generation - Suswandari, Suswandari; Absor, Nur Fajar; Soleh, Mohammad Badrus (Paramita: Historical Studies Journal, 2021)
Technology has evolved so rapidly, one of the contents which are currently popular on social media is the meme. Meme, which was initially for humor, continues to develop into a platform for critical media to distribute knowledge. Historical themes become interesting things to inform through a meme. Meme readers can find historical details through a meme, which makes history themes exciting, so the history teaching process can use memes as a learning medium. The aims of this study are (1) to explore the perceptions of the meme as history learning media; (2) to organize meme parameters that can be used as history learning media; (3) to choose meme content that can be used as history learning media. This study uses a qualitative analysis method with a case study approach as developed by Robert K. Yin. The data in this study were collected from in-depth interviews, participant observation, and documentation study. The data analysis methodology, meanwhile, uses the model of Creswell. This study took ten samples using the purposive sample from History Education students of FKIP-UHAMKA from semesters 3, 5, and 7. The results showed that memes have the power to be a stimulus for their readers to find out more information. Due to the nature of meme that tends to contain jokes, it makes them easy to read. Using memes as a learning tool allows teachers or lecturers to intersperse the historical learning process while still presenting historical facts in an event. Therefore, history learning can be successful and exciting.Teknologi mengalami perkembangan yang begitu cepat, salah satunya adalah media sosial dengan kontennya yang sedang populer adalah meme. Meme yang awalnya hanya berupa penyampaian humor, kini terus berkembang menjadi media penyampaian informasi hingga media kritik. Tema sejarah menjadi hal yang menarik diinformasikan melalui media sosial yang disebut meme. Para pembaca meme dapat mengetahui info kesejarahan, sehingga dapat digarisbawahi bahwa meme dapat dijadikan sebagai media pembelajaran untuk membantu dalam proses pembelajaran sejarah. Adapun tujuan dari penelitian ini adalah (1) menelaah persepsi penggunaan meme sebagai media pembelajaran sejarah; (2) menyusun kriteria meme yang bisa digunakan sebagai media pembelajaran sejarah; (3) untuk menyeleksi konten meme yang bisa digunakan sebagai media pembelajaran sejarah. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus yang dikembangkan Robert K. Yin. Pengumpulan data dilakukan dengan wawancara mendalam, observasi partisipan dan studi dokumentasi. Sementara itu, teknik analisis data menggunakan model Creswell. Sampel penelitian ini adalah para mahasiswa pendidikan sejarah FKIP-UHAMKA menggunakan sampel bertujuan yang berjumlah 10 orang dari semester 3, 5, dan 7. Hasil penelitian menunjukkan bahwa dengan kekuatan meme sebagai stimulus bagi para pembacanya untuk mengetahui suatu informasi dengan pembawaannya yang cenderung berisi humor atau lelucon, sehingga ringan untuk dibaca, guru/dosen dapat menyelingi proses pembelajaran sejarah dengan menggunakan meme sebagai media pembelajaran dengan tetap memberikan fakta sejarah di dalam suatu peristiwa, sehingga pembelajaran sejarah dapat berlangsung dengan baik dan menarik.